2020
DOI: 10.2147/dmso.s255360
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Untreated Depression Among Type 2 Diabetic Patients at Halaba Kulito Hospital, South Ethiopia: A Cross-Sectional Study</p>

Abstract: Background: Depressed type 2 diabetes mellitus patients (T2DM) show poorer compliance with treatment and self-care recommendations than non-depressed T2DM patients. This contributes to poor prognosis and accelerates diabetic-related complications including poor glucose regulation, diabetic retinopathy, neuropathy, nephropathy, and escalated healthcare expenditure. Objective: This study aimed to determine the magnitude of untreated depression and associated factors among people living with T2DM at outpatient di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…Poor glycemic control in T2DM was about twice (AOR = 1.93; 95% CI = 1.05, 3.53) as risky for depression compared to those who had good glycemic control. This nding is consistent with a large-scale study in 21 developing countries (15), independent studies in Peru (46), Indonesia (41), Egypt (16), North Sudan (37), and Halaba (17). In contradict to this nding, study conducted in America (47), Ire land (48), a meta-analysis in China (33),…”
Section: Factors Signi Cantly Associated With Depressionsupporting
confidence: 86%
See 3 more Smart Citations
“…Poor glycemic control in T2DM was about twice (AOR = 1.93; 95% CI = 1.05, 3.53) as risky for depression compared to those who had good glycemic control. This nding is consistent with a large-scale study in 21 developing countries (15), independent studies in Peru (46), Indonesia (41), Egypt (16), North Sudan (37), and Halaba (17). In contradict to this nding, study conducted in America (47), Ire land (48), a meta-analysis in China (33),…”
Section: Factors Signi Cantly Associated With Depressionsupporting
confidence: 86%
“…However, the current prevalence nding was relatively higher than a recent large hospital-based study result from 21 developing countries, which reported 33.1% (15), and a cohort study in China, which reported 29% depression prevalence among T2DM patients (33). The current prevalence is also higher than results of studies done in United States 26.8% (34),Vietnam 23.2% (35), Ghana 31.3% (36), North Sudan 35.6% (37), and Ethiopian studies in Mizan 37.0% (38) and Halaba 29.3% (17). Different age groups in a study of Ghana and using a higher PHQ-9 cut-off point in studies conducted in Mizan and Halaba, respectively might explain the lower depression prevalence in these settings.…”
Section: Magnitude Of Depressionmentioning
confidence: 83%
See 2 more Smart Citations
“…Regarding the duration of T2DM, symptoms of depression tend to increase early after diagnosis and decrease over a few years and then rise with the longer duration of DM, making a j-shaped curve; the rise with the duration of DM may be related to frailty associated with old age and longer duration [22]. Many studies have demonstrated the significant association between depression in T2DM and diabetes-related complications, poor glycemic control, and lack of exercise [23][24][25][26][27]. The family history as a risk factor may be explained by a potential common genetic susceptibility to both T2DM and depression [28], but no study has mentioned a family history of psychiatric illness as a risk factor for depression in T2DM.…”
Section: Discussionmentioning
confidence: 99%